The Exploration of the Experiences and Perceptions of Muslim Women Teachers and Leaders in British State Schools - Noor, Sanaa (2018)
The main purpose for this dissertation is to examine the experiences and perceptions of Muslim woman teachers and leaders in British state schools. To achieve this, the researcher examined the types of challenges and barriers these teachers experienced and how they coped with often being the only Muslim BME woman in a predominantly white team. Using a qualitative research method, the researcher conducted semi-structured interviews with six teachers and leaders, from different London state schools and boroughs, who consider themselves to be Muslims and declared themselves ethnically as Kenyan (1); Somali (1); Pakistani (3); and Turkish (1). The results show that on account of the intersecting facets of her identity Muslim women are simultaneously oppressed in the midst of being awarded opportunities. Due to the interplay of these intersections as well as stereotypical assumptions which impacts attitudes towards Muslim women, she encounters the Muslim penalty, institutional racism and Islamophobia simply on the grounds of being visibly different.